STRES KERJA SERTA HUBUNGANNYA DENGAN MOTIVASI KERJA KARYAWAN PADA DIVISI SALES AND MARKETING PT.XYZ - andres dharma nurhalim (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the relationship between work stress and work motivation on employees of PT. XYZ. This study uses a quantitative approach method. The sample of this study was 53 employees in the sales and marketing division who were selected using the saturated sample technique. The data collection method used is the work motivation and work stress scale. The data analysis technique used the Kendall's Tau-b analysis test with the help of the Statistical package for Social Sciences SPSS 25 for windows program. The results of this study indicate that there is a negative relationship between work motivation and work stress through the Kendall's Tau-b correlation test with an R result of -0.110 and a significant value of 0.036 (p < 0.50). This means that the higher the work stress of the employee, the lower the work motivation of the employee and vice versa. The lower the work stress that employees have, the higher their work motivation.